Characteristics of White Bread with Duckweed Flour (Lemna sp.) Subtitution as Functional Food - Yuriyan, M. Hammam Antar; Haryati, Sakinah; Meata, Bhatara Ayi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
Processed food products like white bread are favored by various segments of Indonesian society. White bread is widely favored because of its delicious taste, affordable price, and convenience. However, the nutritional components of white bread products are generally dominated by carbohydrates with little protein and fiber. One way to enhance the nutritional components and create functional properties in white bread is by substituting wheat flour with duckweed flour. The potential of duckweed as a food ingredient is well-known due to its high protein and fiber content. Duckweed is also known to have the ability to act as a stabilizer, emulsifier, foaming agent, and thickener in added foods. This study aims to determine the optimal amount of duckweed flour substitution for the characteristics of white bread. The method used in this research is a Completely Randomized Design (CRD) consisting of 4 treatment levels (0%, 1%, 3%, and 5%) with 2 replications. This research has two main stages: the production of duckweed flour and the making of white bread. The testing parameters in this study include proximate analysis, crude fiber analysis, swelling power analysis, hardness analysis, slice appearance analysis, hedonic analysis, and Bayesian test. The substitution of 3% duckweed flour (F2) became the best treatment with proximate analysis showing moisture content of 3.47%, ash content of 4.67%, fat content of 2.61%, protein content of 14.09%, and carbohydrate content of 75.18%. Physical analysis showed a hardness of 1.905 N, a swelling power of 135.83%, and a good appearance of the slices.